Mutu Pengelolaan Obat di Puskesmas Kabupaten Lombok Tengah Nusa Tenggara Barat - Almahera Almahera; Titik Sunarni; Ika Purwidyaningrum (FORIKES, 2022)
The community health center is one of the basic health service facilities that is responsible for organizing public health efforts, but in practice it is still constrained in realizing standardized pharmaceutical services. So research is needed that aims to determine the quality of drug administration. This descriptive research was conducted in thirteen community health centers in Central Lombok District. Data taken from primary and secondary sources. There were 28 indicators of drug management and 9 indicators had met predetermined standards. Required item accuracy = 195.40%, item suitability with disease pattern = 76.56%, planning accuracy = 230.26%, psychotropic storage = 85.71%, precursor storage = 66.67%, OOT = 50%, high -alert = 82.36% and drug availability rate = 28.67%. It was concluded that the drug management indicators at the Central Lombok District Health Center did not meet the established standards and improvements needed to be made starting from the planning stage to the control stage.Keywords: community health center; drug management; quality ABSTRAK Pusat kesehatan masyarakat merupakan salah satu fasilitas pelayanan kesehatan dasar yang bertanggung jawab menyelenggarakan upaya kesehatan masyarakat, tetapi dalam pelaksanaanya masih terkendala dalam mewujudkan pelayanan kefarmasian yang terstandar. Maka diperlukan penelitian yang bertujuan untuk mengetahui mutu pengelolaan obat. Penelitian deskriptif ini dilakukan di tiga belas puskesmas di Kabupaten Lombok Tengah. Data diambil dari sumber primer dan sekunder. Ada 28 indikator pengelolaan obat dan 9 indikator sudah memenuhi standar yang telah ditentukan. Ketepatan item permintaan = 195,40%, kesesuaian item dengan pola penyakit = 76,56%, ketepatan perencanaan = 230,26%, penyimpanan psikotropik = 85,71%, penyimpanan prekursor = 66,67%, OOT = 50%, high-alert = 82,36% dan tingkat ketersediaan obat = 28,67%. Disimpulkan bahwa indikator pengelolaan obat di puskesmas Kabupaten Lombok Tengah belum memenuhi standar yang telah ditetapkan dan perlu dilakukan perbaikan mulai dari tahapan perencanaan sampai dengan pengendalian.Kata kunci: pusat kesehatan masyarakat; pengelolaan obat; mutu